Trading Places: How Trade Policy Is Reshaping Multinational Firms' Location - Alejandro G. Graziano; Monika Sztajerowska; Christian Volpe Martincus (CESifo GmbH, 2024)
The recent changes in trade policy have significantly impacted trade flows. There is an ongoing debate on whether and to what extent firms may have also reacted to the new trade barriers by modifying the spatial organization of their multinational production to circumvent them. This paper aims to provide new evidence on whether such a tariff-induced shift in the location patterns of multinational firms has actually taken place. To do so, we exploit the changes in U.S. import tariffs in 2018-2019. The evidence indicates that firms have indeed responded to these new tariffs by adjusting the extensive margin of their multinational production across countries and that both structural factors and trade agreements played an important role in shaping these adjustments.
Keywords: F13; F21; F23; 330; multinational firms; foreign direct investment; trade policy; tariffs